Identifikasi Daerah Rawan Kecelakaan sebagai Dasar Pembuatan Buku Pedoman Teknis Penanganan Kecelakaan (Studi Kasus: Beberapa Ruas Jalan di Wilayah Kota Surabaya Provinsi Jawa Timur) - Dadang Supriyatno (AGREGAT, 2020)
AbstractTraffic accidents are events that are not expected to involve at least one motor vehicle on a road and resulted in material losses, even to swallow the loss of life (source: Kadiyali, 1973). Therefore, the research team was interested in the theme of research related to the identification of Accident-prone Areas/Dots Black Spot as the basis for the creation of a technical Manual Handling accident (Accident Prone Area case study in the city of Surabaya of East Java province) in order to overcome the accident so as not to continue to increase. The purpose of research can determine the condition of the existing road indicated on the accident-prone areas. So that the existing problems in the field can be immediately made known to the handling of the proposal in the form of the Handbook. Methods of research conducted by the research team in this study is to identify existing conditions in order to know all the problems that occur in the field that causes a lot of accidents. The results of the identification / field surveys can be known perangkingan worst location on the basis of the number of accident victims. The location was ranked first to third is streets A.Yani value EAN 1467 (ranking first location) and has a value of 10,003 black spot; Kalianak roads EAN value 1266 (ranking second location) and has a value of 38,662 black spot; roads Mastrip EAN value in 1257 (ranked third) and had a 7138 value of the black spot. Value of the accident rate on the roads.A. Yani of 25.008; Mastrip Streets of 12.746; and Kalianak roads of 1266. Troubleshooting strategies applied divided 3 time periods, i.e. short term strategies, medium-term and long-term. The Division is performed based on the level of difficulty of the work and the magnitude of the costs incurred.Keywords : Identification, EAN, Black Spot, Coping StrategiesAbstrakKecelakaan lalu lintas adalah peristiwa yang diperkirakan tidak melibatkan setidaknya satu kendaraan bermotor di jalan dan mengakibatkan kerugian material, bahkan menelan korban jiwa (sumber: Kadiyali, 1973). Oleh karena itu, tim peneliti tertarik dengan tema penelitian yang berkaitan dengan identifikasi Daerah Rawan Kecelakaan / Titik-titik Hitam sebagai dasar untuk pembuatan teknis kecelakaan Penanganan Manual (studi kasus Daerah Rawan Kecelakaan di kota Surabaya Timur). Provinsi Jawa) guna mengatasi kecelakaan agar tidak terus meningkat. Tujuan penelitian dapat menentukan kondisi jalan yang ada ditunjukkan pada daerah rawan kecelakaan. Sehingga masalah yang ada di lapangan dapat segera diketahui penanganan proposal dalam bentuk Buku Pegangan. Metode penelitian yang dilakukan oleh tim peneliti dalam penelitian ini adalah mengidentifikasi kondisi yang ada untuk mengetahui semua masalah yang terjadi di lapangan yang menyebabkan banyak kecelakaan. Hasil identifikasi / survey lapangan dapat diketahui perangkingan lokasi terburuk berdasarkan jumlah korban kecelakaan. Lokasi yang peringkat pertama hingga ketiga adalah jalan-jalan A.Yani nilai EAN 1467 (peringkat pertama lokasi) dan memiliki nilai 10,003 black spot; Nilai EAN jalan Kalianak 1266 (peringkat kedua lokasi) dan memiliki nilai 38.662 titik hitam; nilai jalan Mastrip EAN di 1257 (peringkat ketiga) dan memiliki 7138 nilai titik hitam. Nilai tingkat kecelakaan di jalan. Yani dari 25.008; Mastrip Streets of 12.746; dan jalan Kalianak tahun 1266. Strategi pemecahan masalah yang diterapkan dibagi 3 periode waktu, yaitu strategi jangka pendek, jangka menengah dan jangka panjang. Divisi ini dilakukan berdasarkan tingkat kesulitan pekerjaan dan besarnya biaya yang dikeluarkan.Kata kunci : Identifikasi, EAN, Black Spot, Strategi Mangatasi